Design of Loan Application Information System at CV. DIKCTA Nusantara Bekasi Barat - Fandy Akmal (ASIAN PUBLISHER, 2024)
A financing institution is a business entity that carries out financing activities in the form of providing funds or capital. This financing institution offers cash loans to its customers like banks. The loan value provided is also quite large, but the requirements and guarantees are lighter than banks, one of which is collateral with a guarantee of motor vehicle ownership. The study entitled Loan Application Information System CV. DIKCTA Nusantara Bekasi Barat aims to determine the flow of loan applications with BPKB collateral at CV. DIKCTA Nusantara Bekasi Barat and to determine the obstacles in the flow of loan applications with BPKB collateral at CV. DIKCTA Nusantara Bekasi Barat and their solutions. The research methods used are Literature Study (Library Research) and Field Study (Field Research), the application software used is Visual Studio Code, XAMPP, MySQL with PHP version 7. With the Loan Application Information System at CV. DIKCTA Nusantara Bekasi Barat, it is expected to facilitate the loan application process.